Relative Toxicity of some Insecticides as Contact Poison against Third Instar Larvae of Hyblea puera (Lepidoptera: Hyblaeidae) - Gupta, B. K.; Borse, Sandhya S. (Indian Forester, 1997)
Eleven insecticides were bioassayed against third instar larvae of Hyblea puera under laboratory conditions. The results are described in this paper.